Coleta, reprodução e larvicultura do Pseudopimelodus mangurus e desenvolvimento embrionário do Pimelodus maculatus e Pseudopimelodus mangurus em diferentes temperaturas. - Arashiro, Dilberto Ribeiro (2018)
The aim of this study was to describe a procedure for sampling, reproduction, and first feeding of the Neotropical catfish Pseudopimelodus mangurus. Wild adult P. mangurus specimens were collected in the Mogi Guassu river, and subsequently, were induced to spawn in laboratory conditions. After hand-stripping the females, the average weight of the oocytes was 143 ± 1.66 g, having an average of 718 ± 49.802 oocytes g-1. The diameter of zygotes was about 1226.354 ± 47.719 µm nonhydrated to 1761.256 ± 26.412 µm after hydration. The fertilization rates were 98.00 ± 0.63%, and the hatching rate were 68.94 ± 11.83%. Three days after hatching, the larvae started exogenous feeding. First feedings were made with 6 different treatments, in which the best results arose with sequential feeding with artemia nauplii, Astyanax altiparanae, and Prochilodus lineatus larvae. This condition resulted in a growth rate of 2012.795 ± 44.891 µm by the tenth day of experiment, higher survival rate (65 ± 0.09%), and a lower cannibalism rate 14 ± 0.03% on the tenth day after exogenous feed. The data obtained in this study is important for reproductive biotechniques and mass production of the endangered catfish P. mangurus.